Physicians' Response and Preparedness of Terrorism-Related Disaster Events in Quetta City, Pakistan: A Qualitative Inquiry - Khilji, Fazal Ur Rehman; Zil-e-Huma,; Baloch, Nosheen Sikander; Shoaib, Maryam; Iqbal, Zaffar; Raziq, Abdul; Sadaf, Nabila; Ainuddin, Syed; Haider, Sajjad; Saleem, Fahad; Iqbal, Qaiser; Hussain, Tanveer; et al. (Frontiers in Public Health, 2022)
Background: Besides catastrophes, infrastructural damages, and psychosocial distress, terrorism also imposes an unexpected burden on healthcare services. Considerably, adequately-prepared and responsive healthcare professionals affirms effective management of terrorism-related incidences. Accordingly, the present study aimed to evaluate physicians' preparedness and response toward terrorism-related disaster events in Quetta city, Pakistan. Methods: A qualitative design was adopted. Physicians practicing at the Trauma Center of Sandeman Provincial Hospital (SPH), Quetta, were approached for the study. We conducted in-depth interviews; all interviews were audio-taped, transcribed verbatim, and analysed for thematic contents by a standard content analysis framework. Results: Fifteen physicians were interviewed. The saturation was achieved at the 13th interview however we conducted another two to validate the saturation. The thematic content analysis revealed five themes and 11 subthemes. All physicians have experienced, responded to, and managed terrorism-related disaster events. They were prepared professionally and psychologically in dealing with a terrorism-related disaster. Physicians identified lack of disaster-related curricula and training, absence of a standardized protocol, recurrence of the disaster, and hostile behaviour of victim's attendants during an emergency as critical barriers to effective terrorism-related disaster management. Among limitations, all respondents mentioned workspace, and resources as a foremost constraint while managing a terrorism-related disaster event. Conclusion: Although physicians understood the abilities and had the required competencies to mitigate a terrorism-related disaster, lack of workspace and resources were identified as a potential barrier to effective disaster management. Based on the results, we propose reconsideration and integration of the medical curriculum, particularly for terrorism-related disaster management, collaboration, and communication among various stakeholders to manage terrorism-related disaster events competently.